PENGARUH BLENDED LEARNING TERHADAP MOTIVASI BELAJAR MATEMATIKA PADA SISWA DI KELAS XI SMK NEGERI 1 ANGKOLA TIMUR TAHUN AJARAN 2021/2022 - Indah Purnama Sari (Program Studi Matematika Universitas Graha Nusantara Padangsidimpuan, 2022)
This study aims to determine whether there is an effect of Blended Learning on the motivation to learn mathematics in class XII TBSM SMK Negeri 1 Angkola Timur. This type of research is an experiment by giving treatment to the research sample group and then given a post-test, as a data collection tool the instrument is a student's mathematics learning motivation questionnaire. The sample in this study consisted of 2 classes of 30 students in class XI TBSM-1 as the experimental class and class XI TBSM-2 as the control class. The results of the questionnaire on students' motivation to learn mathematics obtained an average score of students on the subject of relations and functions of 83.53 and a standard deviation of 10.644 in the experimental class or those given treatment. While in the control class obtained an average value of 76.93 with a standard deviation of 8.925. And after the t-test was carried out on the post-test data of the experimental and control classes, which was used to see whether there was an effect of Blended Learning on the motivation to learn mathematics in class XI TBSM students of SMK Negeri 1 Angkola Timur, it was found that the t-count = 2.602 and t- table = 2.042 for the significance level = 0.05. This shows that the value of t-count > t-table is 2.602 > 2.042 then Ho is rejected and Ha is accepted.